Characterisation and modelling of static recovery process of plain carbon steel - Mohd Hazwan, Kamarudin (2008)
This thesis is an investigation of static recovery process due to different pre – strain, temperature and time on recovery process. In this project, plain carbon steel specimens were subjected to tensile test and heat treatment process. The specimens were the tensile test specimen shape according ASTM E8. Box furnace was used in this project to perform the heat treatment of the specimens. The specimens were heated to a temperature which is below the recrystallization temperature with certain range of time. In this research, the recovery temperature was varied to 100oC, 200 oC, 300 oC and 400 oC. The pre – strain value was varied to 5%, 10%, 15% and 20% which is the value before the specimen break. The time was varied to 1 hour, 2 hours, 3 hours and 4 hours in order to analyze the static recovery process due to different time. The change of stress values were taken before and after static recovery for all variables to calculate the degree of recovery, Xrec by using Friedel’s model equation. The graphs were plotted to analyze the relationship between degree of recovery with these variables. The linear equations that obtained from each graph were compared with Friedel’s model equation in order to calculate the activation energy, Q. In this research, the activation energy for different temperature (1 hour fixed time, 10% pre - strain) was 118 kJ/mol and the value for different time (300oC fixed temperature, 5% pre - strain) was 162 kJ/mol. Finally, the activation energies that obtained were compared with other journal in order to validate the static recovery process of plain carbon steel by using Friedel’s method equation.